PENGARUH KARAKTERISTIK PERUSAHAAN DAN KARAKTERISTIK DEWAN KOMISARIS TERHADAP KEBIJAKAN DIVIDEN - Limbong, Gresita Fikania; Darsono, Darsono (Diponegoro Journal of Accounting, 2021)
This study was aimed to examine the effect of firm characteristics and board of commissioner characteristics on the dividend policy. The dependent variable of this study is dividend policy which is measured by dividend payout ratio (DPR). The firm characteristics proxied by profitability (ROA), leverage (DER), free cash flow, and the board of commissioner characteristics proxied by board size, board independence and board expertise. In addition, firm size and firm growth were used as control variables. The population of this study were the manufacturing company listed on the Indonesia Stock Exchange in the period of 2016-2018. Based on the purposive sampling method, the final sample obtained were 192 companies. Multiple linear regression was used to test the hypothesis in this study.             The results showed that profitability (ROA), free cash flow, board independence and board expertise have a positive and significant effect on dividend policy, whereas leverage (DER) and board size have no significant effect on dividend policy.